STRUCTURAL RESTRUCTURING OF CAPACITIVE LINKS OF HEMOMICROCIRCULATORY STEAM AFTER ACTION OF 1% ETHER OF METACRYLIC ACID - Kramarenko, D.R.; Yeroshenko, G.A.; Nebesna, Z.M.; Lysachenko, O.D.; Boruta, N.V.; Vatsenko, A.V. (World of Medicine and Biology, 2019)
Under experimental conditions, after the action of 1 % solution of methacrylic acid methyl ester on the oral mucosa using the morphometric method, it was established that methacrylic acid esters affect the vessels of the hemomicrocirculatory bed of rats, which is confirmed by a persistent dilatation of venules and is substantiated by a significant increase in outer diameters of the rats 27.76 % and internal by 42.71 % during the experiment, with a decrease in the thickness of the vascular wall by 25.86 %, and is confirmed by a decrease in the Vogenvo index that on 51,10 %. These changes are due to the reaction to the narrowing of the resistive element of the hemomicrocirculatory bed and, as a result, an increase in the overhydration of the amorphous substance of the surrounding interstitium.